Gravity – An Intrinsic Property of Matter! A Qualitative Graviton-Orbital-Band Theory - Malek, Abdul (JOURNAL OF ADVANCES IN PHYSICS, 2018)
All profound theories of nature, life, and society have some philosophical underpinning; the theories of gravity are no exceptions. The theories of gravitation of Isaac Newton and Louis Le Sage were based on mechanical materialism and British empiricism. Albert Einstein developed his geometrical theory of gravity based on idealist Neo-Berkeleyan “positivism” of Ernst Mach. But none of these theories provide, among other things, any tangible intuition into the development of discrete, quantized and the shell like structure of matter from the subatomic to the cosmic, that modern physics, astrophysics and astronomy are revealing in increasing details. A dialectical and qualitative quantum mechanical approach to gravity based on a concept of quantized graviton-orbitals provides an explanation for the cellular structure in the universe.